Aesthetics of Globalization in Daya Pawar's Baluta: Reflexivity and Social Change in Critical Perspective. Issue 1 (May 2020) - Murage, Peter Ndambiri; Makokha, Justus K. S.
This article seeks to discuss the point of intersection between globalization and localization. The study is aimed at discussing the effects of globalization on the lives and the characters exposed in Daya Pawar's powerful book Baluta (translated in English under the same title in 2015 by Jerry Pinto). The characters, who are otherwise well rooted in the traditions practised in their localities, are forced to adapt to the strong waves of change occasioned by modernity. Globalization has occasioned migrants to settle in the localities of Kawakhana and the neighbouring regions. Consequently, popular social joints have sprung up in these localities, prompting the lives of characters to change drastically. Social vices such as betting, alcoholism and prostitution have risen drastically with the increase in clubs, betting dens and brothels. The individual lives of the dwellers of Kawakhana have deteriorated with increased modernization and urbanization. On the brighter side, modern schools have become more popular, with the parents seeing the need of taking their children to school. This element of social change has resulted to the emancipation of the people in the lower castes—the Mahar. Through education, the children of the Mahar have gained economic empowerment, enabling them to break the yoke of tradition that has relegated them to the inferior social position. It is in light of these drastic social changes that this article seeks to explore the aesthetic manifestation of globality, reflexivity and social change.